Ku redefinicji ludobójstwa: realia lokalne - Klein, Dennis (ETHICS IN PROGRESS, 2014)
Looking at local circumstances such as a neighborhood compels a reformulation of genocide. Their exposure of the incremental escalation of assault makes clear that intention, though a necessary condition of genocide, isn’t always a sufficient one, eroding the orthodox definition of genocide itself which too evolves. Locality also takes into account witnesses’ conviction that, though the commission of radical crimes is indefensible and demands prosecution, a post-genocide order can accommodate a human synthesis as well as a post-traumatic coexistence of peoples.